Predictor Corrector Parallel Based on the Geometric Mean Runge-Kutta Formula for Solving Initial Value Problems - Mahmood D. Jasim (مجلة جامعة الانبار للعلوم الصرفة, 2020)
The purpose of this study is to present a new connection of the famous Runge-Kutta methods by using more than one old technique and obtain a new method, which has acceptable results for solving Initial Value problems.